2017
DOI: 10.5562/cca3163
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Discrete and Passive Sampling (Diffusive Gradients in Thin-films – DGT) Approach for the Assessment of Trace Metal Dynamics in Marine Waters – a Case Study in a Small Harbor

Abstract: Two complementary approaches, based on discrete and passive samplings (diffusive gradients in thin-films -DGT), supported by the speciation modeling, were evaluated for the assessment of distribution and operational speciation of trace metals (Zn, Cd, Pb, Cu, Ni and Co) within a small marine harbor (Rijeka, Croatia). Concentrations of dissolved metals were relatively low and comparable to, or slightly above those found in coastal Adriatic region. Compared to higher variability of dissolved metal concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 49 publications
(96 reference statements)
0
5
0
Order By: Relevance
“…This relation is supported by a few studies which found out that the accumulated metal (including Pb) in biota are better correlated with DGT-labile fraction than with dissolved fraction (Kim et al, 2016). (Cindrić et al, 2017). It suggests a strong short-term variability of Pb concentration within the Bay, which is also obvious on temporal profiles of DGT-labile Pb concentrations (Figure 3).…”
mentioning
confidence: 63%
“…This relation is supported by a few studies which found out that the accumulated metal (including Pb) in biota are better correlated with DGT-labile fraction than with dissolved fraction (Kim et al, 2016). (Cindrić et al, 2017). It suggests a strong short-term variability of Pb concentration within the Bay, which is also obvious on temporal profiles of DGT-labile Pb concentrations (Figure 3).…”
mentioning
confidence: 63%
“…Trace metals bioavailability is strongly controlled by the presence of dissolved organic ligand, especially in marine waters (Louis et al, 2009; Bruland et al, 2013). We considered here DOC concentrations and the dissolved fraction of trace metals, which is closer to the bioavailable fraction than the total concentration (Paquin et al, 2002; Cindrić et al, 2017) and consequently allow a more reliable assessment of their roles. Nevertheless, we neither evaluated the speciation of the main trace metals nor DOC composition in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, labile TMs concentrations, considered to be more representative from the bioavailable fraction (Caillat et al, 2014;Han et al, 2014;Kim et al, 2016), were assessed at every site and depth using three passive samplers (diffusive gradients in thin-films -DGT) immersed for the whole survey (n = 30). DGT devices, sample preparation and analytical methods for multi-element analysis in DGT eluates were described in Cindrić et al (2017) and are summarized in Supplementary Material.…”
Section: Environmental Measurementsmentioning
confidence: 99%